Demonstration of a Coupled Metabolism–Efflux Process at the Choroid Plexus as a Mechanism of Brain Protection Toward Xenobiotics - Strazielle, Nathalie (J Neurosci, 1999)
Brain homeostasis depends on the composition of both brain interstitial fluid and CSF. Whereas the former is largely controlled by the blood–brain barrier, the latter is regulated by a highly specialized blood–CSF interface, the choroid plexus epithelium, which acts either by controlling the influx of blood-borne compounds, or by clearing deleterious molecules and metabolites from CSF. To investigate mechanisms of brain protection at the choroid plexus, the blood–CSF barrier was reconstituted in vitro by culturing epithelial cells isolated from newborn rat choroid plexuses of either the fourth or the lateral ventricle. The cells grown in primary culture on semipermeable membranes established a pure polarized monolayer displaying structural and functional barrier features, (tight junctions, high electric resistance, low permeability to paracellular markers) and maintaining tissue-specific markers (transthyretin) and specific transporters for micronutriments (amino acids, nucleosides). In particular, the high enzymatic drug metabolism capacity of choroid plexus was preserved in the in vitro blood–CSF interface. Using this model, we demonstrated that choroid plexuses can act as an absolute blood–CSF barrier toward 1-naphthol, a cytotoxic, lipophilic model compound, by a coupled metabolism–efflux mechanism. This compound was metabolized in situ via uridine diphosphate glururonosyltransferase-catalyzed conjugation, and the cellular efflux of the glucurono-conjugate was mediated by a transporter predominantly located at the basolateral, i.e., blood-facing membrane. The transport process was temperature-dependent, probenecid-sensitive, and recognized other glucuronides. Efflux of 1-naphthol metabolite was inhibited by intracellular glutathione S-conjugates. This metabolism–polarized efflux process adds a new facet to the understanding of the protective functions of choroid plexuses.